(untitled) (Scientific journal of the Fergana State University, 2023)
This article is devoted to a comparative analysis of the field of verbal and nonverbal units that verbalize the concept of "gender" in English and Uzbek, which explores the similarities and differences of genderological units in both languages, revealing the factors that require them.